2018
DOI: 10.1186/s13071-018-2732-9
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial trends in insecticide resistance in Anopheles arabiensis in Sudan: outcomes from an evaluation of implications of insecticide resistance for malaria vector control

Abstract: BackgroundLong-lasting insecticidal nets (LLINs) (with pyrethroids) and indoor residual spraying (IRS) are the cornerstones of the Sudanese malaria control program. Insecticide resistance to the principal insecticides in LLINs and IRS is a major concern. This study was designed to monitor insecticide resistance in Anopheles arabiensis from 140 clusters in four malaria-endemic areas of Sudan from 2011 to 2014. All clusters received LLINs, while half (n = 70), distributed across the four regions, had additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…The study shows that IRS or LLINs [even at varying degrees of coverage (Table 3)] may not be able to reduce malaria incidence further in areas with a low malaria incidence. The study suggests that using LLINs and IRS alone in areas with low malaria incidence may not be able to substantially reduce malaria incidence or eliminate malaria, as has also been suggested in a recent review and modelling studies [14, 30, 31].…”
Section: Discussionmentioning
confidence: 68%
“…The study shows that IRS or LLINs [even at varying degrees of coverage (Table 3)] may not be able to reduce malaria incidence further in areas with a low malaria incidence. The study suggests that using LLINs and IRS alone in areas with low malaria incidence may not be able to substantially reduce malaria incidence or eliminate malaria, as has also been suggested in a recent review and modelling studies [14, 30, 31].…”
Section: Discussionmentioning
confidence: 68%
“…Several studies have reported spatial variation in resistance within a country, but these studies haven't analysed the spatial trends behind this variation [11,12]. In addition, time series of resistance data have shown changes over time at the location of sentinel sites [13][14][15][16][17][18][19][20]; however, only one study has investigated temporal trends across Africa [7]. This study generated a single trend over time for the whole continent, for each species and insecticide, and did not investigate differences in trends between locations.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2015, deltamethrin has been the only pyrethroid reported to be used in mass IRS campaigns along with DDT and other non-pyrethroid insecticides [4]. Several studies have demonstrated a local increase in insecticide resistance in field mosquito populations following the implementation of LLINs, IRS, or both [19,20,[24][25][26] although in other locations evidence of higher resistance after the introduction of these interventions was not found [24,27]. Associations between agricultural pesticide use and insecticide resistance have also been found [21,28], and there is evidence that pesticide contamination of water bodies is a source of selection pressure for resistance acting on mosquito larvae [29].…”
Section: Introductionmentioning
confidence: 99%
“…Sources of insecticides in the environment include the application of insecticide-based vector control interventions for public health, such as LLINs and IRS, and the application of agricultural insecticides, which include the same insecticide classes as those used in vector control 11 . Several studies have demonstrated a local increase in insecticide resistance in field mosquito populations following the implementation of LLINs, IRS, or both 12, 13, 14, 15, 16 although in other locations evidence of higher resistance after the introduction these interventions was not found 12, 17 . Associations between agricultural pesticide use and insecticide resistance have also been found 11, 18 , and there is evidence that pesticide contamination of water bodies is a source of selection pressure for resistance acting on mosquito larvae 19 .…”
Section: Introductionmentioning
confidence: 99%